IMPLEMENTASI FUNGSI ADMINISTRASI KESISWAAN DALAM MENINGKATKAN EFISIENSI PELAYANAN DI SMK NEGERI 4 KOTA JAMBI - Carmelira Angel Gulo; Mulyadi Mulyadi; Yudo Handoko (STKIP Pesisir Selatan, 2026)
This research aims to explore how student administration is implemented to improve service efficiency at SMK Negeri 4 Kota Jambi. Student administration plays an important role in facilitating services for students and organizing student data in an orderly and systematic manner. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation involving the school principal and student administration staff as informants and student. The data were analyzed through several stages, including data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the implementation of student administration at SMK Negeri 4 Kota Jambi has been carried out effectively and has contributed to improving service efficiency through more systematic student data management, faster administrative procedures, and greater accuracy in data processing. However, the study also found challenges related to the limited number of human resources in managing student administration. The novelty of this research lies in its analysis of the implementation of student administration with a focus on improving service efficiency using indicators of speed, accuracy, and staff productivity within the vocational school environment.